An Inquiry into the Principles of Political Oeconomy (Vol. 1 of 2) : Being an essay on the science of domestic policy in free nations. In which are particularly considered population, agriculture, trade, industry, money, coin, interest, circulation, banks, exchange, public credit, and taxes - Steuart, James, Sir, 1712-1780 (Salt Lake City, UT : Project Gutenberg, 2019)
"An Inquiry into the Principles of Political Oeconomy (Vol. 1 of 2)" by Sir James Steuart is a comprehensive scientific publication written in the mid-18th century. This work aims to systematically establish the principles underpinning economic practices within states, particularly focusing on domestic policies related to population, agriculture, trade, and finance. The author seeks to provide insight into how various economic factors interconnect and influence one another, thereby aiding policymakers in understanding their implications for society. The opening of the book presents a preface where Steuart expresses his humility and apprehension regarding the scope of his work, which he feels is vast in comparison to his own abilities. He shares the insights he has gathered from years of travel and study across different nations, emphasizing the unique cultural contexts that shape political oeconomy. Steuart$1 (Bs intent is to compile these observations while maintaining objectivity, as he aims to outline a framework that can be built upon by future scholars. The early chapters then delve into the relationship between population growth and agricultural practices, highlighting the fundamental need for sustainable food production to support societal prosperity. (This is an automatically generated summary.)s
Release date is 2019-10-03
KD Weeks, MFR and the Online Distributed Proofreading Team
Keywords: Economics